(3bGfhf GdYdeGA aj OjhGf GdaVdGAs - (3oWoQrbLj nRGnOrg , eMeO Hf eMehO,J (B1068 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi gOGfG HCcd GdYfGjI hGdgOGjI s
(3QJHg GdeDda Ydi ebOeI hSJI aUhd hNGJeIs
(3ai XgQ GdhQbI GdChdi efgG cJGHg JajO CfgG cGfJ ehbhag HEMOi GdeOGQS HJGQjN SfI (B1194s
(3cJGH ai JGQjN ePgH CHj MfjaI heTGgjQ GdePgH hJQGLe eDdajgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B89 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B3s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B646 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B202 s
Keywords: (3GdJGQjNs